Physical Quality of Ecoprint Leather Using Epsom Salt Mordant - Pancapalaga, Wehandaka; Widodo, Wahyu; Adiyastiti, Bayu Etti Tri (Universitas Djuanda, 2025)
The objective of this study was to determine the physical quality of ecoprint tanned leather using Epsom salt mordant compared to non-Epsom salt mordants. This research was conducted experimentally by applying different mordants, including Epsom salt mordant, Sodium acetate mordant mordant, and Acetic Acid mordant, in the ecoprinting process on leather material. The study used 9 pieces of crust-tanned sheep leather. The treatments were as follows: P1 = Epsom salt mordant, P2 = Sodium acetate mordant mordant, P3 = Acetic Acid mordant. The research design followed a Completely Randomized Design (CRD) with three treatments and five replications. The observed variables included color fastness to wet and dry rubbing, as well as the physical quality of ecoprinted leather, which consisted of tensile strength, elongation, stitch strength, and tear strength. Data analysis was conducted using ANOVA and Duncan's Multiple Range Test. Results The study found a highly significant effect (P<0.01) of Epsom salt mordant, sodium acetate mordant, and Acetic Acid mordant on wet rubbing fastness, dry rubbing fastness, and the physical quality of leather, including tensile strength, elongation, stitch strength, and tear strength. Conclusion The use of Epsom mordant in the ecoprint process on leather media provides the best physical quality compared to the use of non-Epsom mordant. The quality of ecoprinted leather treated with Epsom salt mordant met the SNI 4593:2011 standard for sheepskin/goatskin jacket leather.